Pengaruh Kepemimpinan Transformasional terhadap Kinerja Karyawan pada Sektor E-Commerce: Studi Kasus pada Perusahaan Start-up di Kota Palembang Indonesia - Maiza Fikri; Fartina Destikarini; Januar Ida Wibowati; Basron Basron; Efniar Efniar (MAMEN: Jurnal Manajemen, 2025)
This study aims to analyze the influence of transformational leadership on employee performance by considering the role of digital competence in the e-commerce start-up sector in Palembang, Indonesia. Using a quantitative approach, data were obtained through a survey with 120 respondents who are start-up employees in Palembang. Analysis was conducted using validity and reliability tests, one-way ANOVA, and two-way ANOVA to examine the interaction between variables. The results show that transformational leadership has a significant effect on employee performance, with the inspirational motivation dimension as the dominant factor. Digital competence has also been shown to improve performance, especially in the aspects of digital literacy and digital communication, although technology adaptation remains a challenge. Furthermore, the interaction between transformational leadership and digital competence produces a significant synergistic effect, where the combination of high levels of transformational leadership and high digital competence results in the highest average performance. These findings provide practical implications that e-commerce start-ups in Palembang need to integrate transformational leadership training programs with employee digital competence development as a strategy to improve performance and competitiveness. This study enriches the modern leadership literature with empirical evidence from the local Indonesian context.